Pelestarian Budaya Lokal: Peran Bersih Desa Dan Langen Bekso Dalam Menanamkan Cinta Tanah Air Di Desa Lengkong Kabupaten Nganjuk - Purnamaningtyas, Dwi Yusta; Widodo, Wahono; Istiq’faroh, Nurul (CV. Kurnia Grup, 2024)
Preserving local culture is important to maintain national identity and foster a sense of love for the country, especially in the midst of increasingly strong globalization. This research was conducted to understand the role of the Bersih Village tradition and Langen Bekso art in instilling love of the homeland in Lengkong Village, Nganjuk Regency. Clean Village is an annual ritual that aims to honor ancestors and maintain community harmony, while Langen Bekso is a dance art that is an expression of local culture and identity. The research method used is descriptive qualitative with data collection techniques through observation, interviews and documentation. The research subjects consisted of community leaders, village heads, youth representatives and village residents. The research results show that these two traditions have a significant role in fostering a sense of love for the country. The Clean Village tradition encourages people to maintain the values ​​of mutual cooperation and kinship, which are part of local wisdom. Meanwhile, Langen Bekso acts as a cultural education medium, where the younger generation can learn about noble values ​​and local cultural identity. The involvement of the younger generation in these two activities is also an effective means of preserving and passing on local culture from generation to generation. The conclusion of this research confirms that Bersih Desa and Langen Bekso in Lengkong Village have an important contribution to preserving local culture and strengthening national identity. This tradition needs to be maintained and developed so that it remains relevant in the future.